Access to oral health services in children under twelve years of age in Peru, 2014 [Acceso a servicios de salud dental en menores de doce años en Perú, 2014] - Hernández-Vásquez, A. (2016)
The aim of the study was to explore the patterns of dental health services access in children under twelve years of age in Peru. Data from 25,285 children under 12 years who participated in the Demographic and Family Health Survey of 2014 were reviewed. An exploratory spatial analysis was performed to project the proportions of children with access to dental health services, according to national regions, type of health service and urban or rural place of residence. The results show that of the total sample, 26.7% had access to dental health services in the last six months, 39.6% belonged to the age group 0-4 years, 40.6% lived in the Andean region and 58.3% lived in urban areas. The regions of Huancavelica, Apurimac, Ayacucho, Lima and Pasco had the highest percentages of access nationwide. In conclusion, there is low access to dental health services in the population under 12 years of age in Peru. The spatial distribution of access to dental health services allows regions to be identified and grouped according to similar access patterns, in order to better focus public health actions.